Growing rice in controlled environments. (15th May 2015) - Köhl, K.
Abstract Rice (Oryza sativa) is less frequently used in basic research than Arabidopsis, although rice is a valuable model system for many monocot crops and possesses a high genetic variability in physiologically as well as agriculturally relevant features such as abiotic stress tolerance, nutrient efficiency and flower time control. A reason is the seemingly difficult cultivation of rice outside the rice production area. This review aims to assist newcomers to the field to develop cultivation protocols for their local controlled environment. The main challenges are high light demands, photoperiodicity and low micronutrient efficiency. The nutrient efficiency problem can be overcome by adding micronutrient fertiliser to potting substrates and keeping the soil waterlogged to increase micronutrient availability and mobility. Cultivation of rice on adjusted hydroponic solutions with high iron concentration provides the basis for successful heavy isotope labelling. Many rice cultivars need high light intensities in combination with short‐day conditions to complete their life cycle. However, some photoperiod‐insensitive cultivars will flower even under relatively low light intensities. In highly photoperiod‐sensitive cultivars, like Nipponbare, flowering can be induced by a limited period of short‐day treatment in the sensitive period, after which the cultivation can be continued in long‐day conditions. The life cycle of many cultivars is completed in 90 to 120 days, its length being thus comparable to Arabidopsis and shorter than in other cereals. In conclusion, with the right cultivation technique, rice is an amiable model species for researchers beyond the rice area too.